The N276 glycosylation site is required for HIV-1 neutralization by the CD4 binding site specific HJ16 monoclonal antibody. - Sunita S Balla-Jhagjhoorsingh (PLoS ONE, 2013)
Immunogen design for HIV-1 vaccines could be based on epitope identification of naturally occurring neutralizing antibodies in infected patients. A tier 2 neutralizing monoclonal antibody (mAb), HJ16 recognizes a new epitope in the CD4 binding site (CD4bs) region that only partially overlaps with the b12 epitope. We aimed to identify the critical binding site by resistance induction in a sensitive primary CRF02_AG strain. In four independent dose-escalation studies, the N276D mutation was consistently the only alteration found and it was confirmed to be responsible for resistance to HJ16 by site-directed mutagenesis in envelopes (envs) of the homologous CRF02_AG, as well as of a subtype A and a subtype C primary isolate. This mutation removes an N-linked glycosylation site. The effect of N276D was very selective, as it failed to confer resistance to a range of other entry inhibitors. Remarkably, sensitivity to the CD4bs VRC01 and VRC03 mAbs was increased in the N276D mutated viruses. These data indicate that binding of the CD4bs specific HJ16 mAb critically depends on the interaction with the N276-glycan, thus indicating that HJ16 is the first glycan dependent CD4bs-specific mAb.